Confirmatory factoral validity of public housing performance evaluation constructs - B. Ishiyaku,; R. Kasim,; A.I. Harir, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aim of this study is to identify the housing features based on their tangible, intangible and component characteristics using occupants’ experience and confirm the factorial validity of the building features with a view to develop a valid and reliable measurement model that can be used effectively in public housing performance evaluation. The study was based on survey of public housing occupants’ experience carried out in Gombe metropolis, Gombe State, Nigeria. Two constructs of tangible and intangible building experience were developed as independent variables, with building components experience construct as dependent variable and validated using AMOS software Version 21. The study confirmed the factoral validity of the constructs, hence provided a better understanding of the housing features and components. The validated constructs in this study are useful for public housing performance evaluation, housing market analysis and public housing policies to improve public housing performance and achieve sustainability.